أثر الفساد على الاستثمارات الاجنبية المباشرة البينية في البلدان الناشئة "دراسة قياسية باستخدام نموذج الجاذبية" - غربي طارق; خضير عقبة; مصطفاوي علي (جامعة الوادي University of Eloued, 2024)
Through this study, we tried to answer the proposed problem, which revolves around measuring the impact of corruption on intra-regional foreign direct investment in emerging countries. Seven emerging countries were selected, and the study relied on a set of corruption indicators, represented by the corruption perceptions index, control of corruption, and good governance. As for economic development, the following indicators were chosen, which are the per capita GDP, the exchange rate, and inflation, in addition to the distance index, trade openness, and the cost of starting a business index, and based on the gravity model, as we used the PPML model, and the stata16 program was used. To measure the impact of corruption on intra-state foreign direct investment flows, the results showed that corruption does not help the flow of foreign direct investment in emerging countries, while corruption helps in the flow of direct investments outside these countries, while trying to control corruption in these countries, enact laws, and impose authority Judiciary and transparency will hinder the flow of these intra-regional foreign direct investments to these emerging countries.
The Impact of Corruption on Intra-Foreign Direct Investments in Emerging Countries "An Econometric Study Using the Gravity Model "
Keywords: الاستثمار الأجنبي المباشر; الفساد; الدول الناشئة; foreign direct investment; corruption; emerging countries